Possibility of correction of the blood-heart barrier damage as a consequence of the impact of the SARS-CoV-2 virus on the cardiovascular system in patients with coronary artery disease in combination with COVID-19. - Netiazhenko , Vasyl; Mostovyi , Serhii; Mikhaliev , Kyrylo; Safonova , Olga (The Ukrainian Scientific Medical Youth Journal, 2024)
damage to the blood-heart barrier (BHB) and endothelial dysfunction is a characteristic feature of congestive (cardiopulmonary) chronic heart failure (CHF), the main cause of death in elderly people with CHF caused by new coronavirus variants (SARS-CoV-2), but the mechanism of this phenomenon remains unclear. The aim of this project is to determine the mechanism of BHB damage in coronary artery disease (CAD) with COVID-19, as well as the possibility of its correction with the use of sulodexide. The endocardial endothelium (EE) is a barrier that prevents blood leakage from the endocardium to the interstitium; however, this barrier is impaired during the course of COVID-19 in patients with CAD. Previous studies have shown that one of the pathophysiological mechanisms is the activation of matrix metalloproteinases (MMPs) in CAD with CHF. MMP-9 degrades connexins, which leads to EE dysfunction. One study [Rubens P. et al. 2021] found a juxtacrine connection of EE with the myocyte and mitochondria (Mito), but how this works is still an open question. Materials and methods. We examined 65 patients with coronary artery disease diagnosed with COVID-19. Patients were divided into two groups: Group I (n=35) - patients who had been taking sulodexide at a dose of 500 LE x 2p/day for 6 months against the background of standard therapy of coronary artery disease; Group II (n=30) - patients without sulodexide. Echocardiography and laser Doppler flowmetry were performed at baseline and 6 months later. Echocardiography at the time of inclusion in the study revealed that 30 (50%) patients in group I and 14 (47%) patients in group II had reduced left ventricular ejection fraction (LV EF) values of 40 to 50%. After 6 months of treatment with sulodexide, a tendency to improve LV systolic function and decrease in left ventricular myocardial mass index (LFMMI) was noted in patients of group I. There were no differences between the groups at the time of inclusion in the study in terms of the level of the capillary flow reserve – occlusion test (CFRo) and the capillary flow reserve – nitroglycerin test (CFRn). A repeated study of CFR revealed a significant increase in CFRo and CFRn levels only in group I. In patients of group II, no significant changes in CFRo and CFRn were found. An inverse relationship between the level of CFRo and C-reactive protein (CRP) was found in patients of group I (r=0.52, p<0.05). After 6 months of treatment, plasma CRP concentrations decreased significantly: from 17.7 [1.3; 50.1] to 5.7 [1.0; 12.0] mg/L in group I (p=0.01) and from 14.2 [1.2; 27.0] to 4.2 [1.0; 11.0] mg/L in group II (p=0.01). No significant correlations between CRP level and CFRo after 6 months of treatment were found. There were correlations of CFRo and CFRn with left ventricular systolic function, as well as inverse relationships with the size of the left and right ventricles and systolic pressure in the pulmonary artery. There was a tendency to improve systolic and diastolic left ventricular function in the first group, where sulodexide was used, and no significant changes in echocardiography were noted in the second group. At the initial examination of patients, the ratio of CFRo and CFRn had no significant differences. After 6 months of treatment, a significant increase in the ratio of CFRo and CFRn was observed only in patients taking sulodexide, and no positive dynamics of this ratio was observed in group II. The results indicate that MMP-9 activation, endothelial damage, endothelial-myocyte (E-M) uncoupling, and mitochondrial-myocyte uncoupling in heart failure in patients with CAD combined with COVID-19 were detected to a significant extent; however, treatment with sulodexide successfully mitigated the destructive changes in the heart in CAD with CHF. The results obtained are directly relevant to the range of cardiac manifestations and phenotypes arising from COVID-19 complications in people with CAD. Conclusion. The obtained results confirm the improvement of microcirculation, as well as a tendency to improve systolic function and left ventricular myocardial mass index after 6 months of sulodexide treatment in patients with coronary artery disease with preserved and moderately reduced left ventricular ejection fraction (LV EF) who have undergone COVID-19. The described effects of improving endothelial function, as well as improving the state of the blood-brain barrier due to the use of sulodexide, make it possible to recommend the use of this drug in the category of patients with CAD to reduce the negative impact of COVID-19 on the cardiovascular system.